Use of herbs and spices for food preservation: advantages and limitations. (December 2015) - Martínez-Graciá, Carmen; González-Bermúdez, Carlos Alberto; Cabellero-Valcárcel, Ana María; Santaella-Pascual, Marina; Frontela-Saseta, Carmen
Highlights: Many spices and herbs have antimicrobial effects on plant and human pathogens. Active compounds of antimicrobials work in different and diverse ways to stop microbial growth. High levels of spices and herbs are necessary to inhibit growth in food. Necessary research area: to determine which natural antimicrobials or emerging technologies may act synergistically with herbs and spices combinations. Abstract : Spices and herbs are gaining importance in recent years as potential sources of natural food preservatives due to the growing interest in the development of safe and effective natural food preservation. The amounts of phenolic compounds play a major role in their antimicrobial effects but it also depends of a wide variety of intrinsic and extrinsic factors, that must be characterized before the use of herbs and spices as ingredients. This fact leads to require a high concentration of these plant extracts to inhibit the microbial growth in foods causing negative organoleptic effects and limiting their use. The synergistic interaction with physical treatments or different natural additives may increase their antibacterial efficacy at sufficiently low concentration, which may reduce their adverse effects and facilitate their use in food preservation system.